Etiological Diagnosis of Non-Traumatic Myelopathies: Experience in a Tertiary Health Care Center in Bangladesh - Kundu, Narayan Chandra; Quraishi, Firoz Ahmed; Sen, Moushumi (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background: The relative frequency of non-traumatic compressive and non-compressive myelopathies and their etiologies have not been evaluated extensively in Bangladesh. This study was aimed to identify the etiological diagnosis of non-traumatic myelopathies. Methods: One hundred cases of non-traumatic myelopathic admitted patients were prospectively studied during 2009- 2012 in the neurology ward of Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh. Patients underwent a detailed clinical evaluation followed by laboratory investigations and neuroimaging studies. Results: Among 100 cases, 46 patients (male 41 and female 5) presented with quadriparesis and 54 patients (male 30 and female 24) presented with paraparesis. Duration of symptoms before presentation to the hospital was considerably higher in quadriparesis compared to paraparesis (230.09 ± 31.16 days VS 136.82 ± 21.77 days; p value = 0.016). There were no significant differences in the number of patients admitted between compressive and non-compressive groups (p value – 0.4035). Common etiologies observed in this study were vertebral disc disease (23%), spinal cord tumor (15%), Pott’s disease (15%), acute transverse myelitis (13%) and motor neuron disease (11%). Conclusion: Vertebral disc disease, spinal cord tumors, infection (Pott’s disease), post infectious condition (ATM), and neurodegenerative disease (MND) are mostly responsible for myelopathies. J Bangladesh Coll Phys Surg 2018; 36(2): 53-58